Investigation of effect of bakelite on mechanical properties of hot mix asphalt mixes - a full factorial design experiment - Ali, Yousaf; Hussain, Muhammad; Riaz, Kashif; Yousaf, Adnan; Tufail, Rana Faisal; Navandar, Yogeshwar V; Rayed, Ashraf Mahmud; Shah, Syed Mustafa Ali (Penerbit Universiti Kebangsaan Malaysia, 2021)
In Pakistan, mostly flexible pavements are constructed which have a higher susceptibility to rutting, moisture damage and stripping. Under current economic conditions, one such solution to overcome this is the addition of economical and locally available additives in the bitumen being produced by our refineries. This study investigates the effects of bakelite as an additive on various mechanical properties. Bakelite is a high-density plastic, cost-effective and locally available material. The modified Hot Mix Asphalt (HMA) specimens were prepared with (2%,4%,6%,8%,10%,12%) Bakelite by weight of optimum binder content found using Marshall Mix design. Performance tests, including Marshall Stability and flow. Retained stability and Resilient Modulus tests were performed to check the performance of modified mixes. The test results revealed that a modified mix containing 6% Bakelite by weight of optimum bitumen content provides the best resistance against moisture damage, rutting and enhancing the HMA mix's stability than the other modifier percentages. The Marshall stability and quotient values of the modified mix increased by almost 22% and 44% respectively. The results showed an increase of 3.5% in the tensile strength ratio indicating an increase in the capability of HMA to resist moisture-induced damage and strength retention. The resilient modulus test was then performed under different conditions, i.e., bakelite (0% & 6%), temperature (25˚C &40˚C) and load duration (100 ms & 300 ms) and analyzed by full factorial design experiment. The factorial analysis showed that Bakelite content is the most significant factor affecting the MR and, ultimately, the strength of the HMA mix. The Resilient modulus test results showed a 20% increase for the modified mix containing 6% Bakelite as compared to the conventional mix. Therefore, it is concluded that the addition of bakelite as an additive in hot mix asphalt mixes gives better results regarding pavement performance.